Early Fault Detection in FOC Driven Induction Motors: A Case Study - Isabela O. Zaparoli; Arismar M. G. Junior; Marco Tulio A. Evo; Diogo S. C. Souza; Helder de Paula (IEEE Access)
Across various productive sectors, failures in electric motors can lead to financial losses, poor production quality, and accidents. Even though motors in high-performance/precision applications are controlled in a closed loop, this category of drive is the least explored in the literature when the subject falls on the detection of inter-turn stator insulation faults, despite closed loop being the most complex among such systems. This complexity arises as the closed-loop control structure drastically modifies or even conceals fault signatures, thus making identification extremely difficult. In this context, among the methodologies currently developed, while considering the existing literature, one specific methodology has shown promising results, making it attractive for practical applications-Gama index. The work presented by those authors significantly contributed to the area of fault detection by proposing the fault index called Gama. However, this study did not address important issues related to the problem that are crucial for validating the fault index presented in that work. Therefore, the present article adds value to the area of fault detection by developing a complementary case study to characterize the performance and accuracy of the Gama index under different situations. These situations include the application of a different control structure for motor drive, the consideration of mechanical faults occurring in the motor simultaneously with the inter-turn short-circuit, along with the application of the technique to a motor with a higher power rating, and, finally, the operation of the machine at different speeds.